Perilaku Sadar Halal pada Generasi Muslim Milenial - Hisan Mursalin (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The rapid growth of the Indonesian Muslim millennial generation population is not directly proportional to the development of their knowledge about halal products. This causes the millennial generation to lack awareness of the importance of consuming halal products. In this regard, this article aims to explore the factual conditions in the millennial generation regarding halal awareness, by including an explanation of the halal product guarantee policy in Indonesia. In this research, a qualitative approach and literature study methods were applied. The research results show that the level of knowledge of the Indonesian millennial Muslim generation regarding halal product provisions is still relatively low. Educational activities and the introduction of halal products have not yet been intensively carried out. This fact shows that the current level of halal awareness among the Indonesian Muslim millennial generation is still relatively weak.